Diagnostico turístico de la comunidad receptora del cantón Buena Fe - Macias Campuzano, Gilda Narcisa (2022)
This study seeks to answer what is the situation of the tourism system around the receiving community of the Canton of Buena Fe? Where its general objective is to analyze the current tourist situation of the receiving community of the Canton of Buena Fe, through this study the perspective that the receiving community has around tourism in the Canton will be taken in such a way that a survey of the community was carried out through descriptive research, using the quantitative method where it was obtained as a result that the Canton has the services of the tourism system, highlighting that there are resources to make the Canton a center of tourism development, however there is ignorance about tourism planning and the strategies that authorities must implement to have a development, tourism, economic and social of the aforementioned